简易高压电缆除冰设备的研制 - 程光明; 姜鹏; 姜兆文; 吴雪; 王立军 (Jixie Chuandong, 2010)
Based on the analysis of the current world wide of deicing methods for researches the high voltage transmission line,a new and simple high voltage transmission line deicer is brought forward and a model is designed and built.Having adopted the mechanisms such as separate upper and lower box bodies,scalable drive shaft,and wheel groups holding the cable up and down,the machine can suspend on cables reliably and advance steadily.When advancing,the machine can erase the covering ice on cable by using the high-speed rotating wheel hob at the same time.After a series of tests,it is confirmed that the machine has the following features:reasonably structured,compact,and user-friendly,which provides a brand-new method for the further development of cable de-icing equipment and has certain value.